Perancangan Sistem Jemuran Pakaian Otomatis Berbasis Teknologi Internet of Things (IoT) - Mutiara Majid; Resa Pramudita (Jurnal Ilmiah Teknologi Infomasi Terapan, 2024)
Drying clothes is an activity that is generally carried out outdoors using sunlight to speed up the drying of clothes. Some people who do a lot of activities outside the home often leave their clothes hanging all day. Along with the erratic changes in seasons, sudden rain can cause clothes that have been dried in the sun to become wet again due to exposure to rainwater. To overcome this problem, automatic clothes drying system based on Internet of Things (IoT) technology was created using LDR sensors and rain sensors. This system uses the Blynk application so that it can be monitored and controlled directly. Wemos D1 R32 is used as a communication medium between the device and the Blynk application. The results of this research are that the clothesline can enter the room when the LDR sensor detects that it is dark or when it is raining and when the user orders the clothesline to enter via the Blynk application